Lecturing as Pedagogical Communication Practice in the Film Wild Child: A Flanders Interaction Analysis Categories - Rizka Sakinatun Anisa; Yeny Prastiwi; Nur Hidayat (Humanitatis : Journal of Language and Literature, 2026)
Communication in the classroom is a fundamental aspect of the learning process. One of the dominant forms of communication used by teachers is teacher talk. Teacher talk is the language a teacher uses to interact with students. To better understand teacher talk, the study aims to examine the function of lecturing as a pedagogical communication practice in learning, as represented in the film Wild Child. Film was chosen as the data source for this study because it provides context for interactions between teachers and students, not only inside the classroom but also outside it. This study uses a descriptive qualitative method, with data sources consisting of teacher talk containing lecturing practices in the film. Data were collected through observation and dialogue recording, and then analyzed with a focus on the pedagogical function of lecturing across various interaction contexts. The results of the analysis show that lecturing consistently appears in various pedagogical contexts, such as explaining values and authority, introducing institutional rules, explaining procedures and norms, clarifying situations and teacher interpretation, conveying facts and opinions, and introducing learning activities. These findings indicate that lecturing does not merely serve as a means of conveying information. Lecturing also plays a role in asserting teachers’ pedagogical authority, guiding students’ interpretations of situations and applicable norms, and framing students’ understanding of acceptable behavior and learning expectations. Thus, the dominance of lecturing in the pedagogical interactions depicted in the film not only reflects a teacher-centered learning orientation but also demonstrates lecturing’s role as a pedagogical communication practice that shapes the meaning, values, and structure of classroom interactions. This study emphasizes the importance of understanding lecturing contextually as a complex and meaningful pedagogical communication practice.